The Impact Of A Proposed Curriculum For Teaching The General Arabic Language Subject According To Academic Accreditation Standards On The Achievement Of Female Students In The Faculties Of Education For Girls (Journal of the College of Basic Education, 2024)
The current research aims to identify "building a proposed curriculum for teaching the subject of the general Arabic language for departments other than the specialization of the colleges of education for girls according to the standards of academic accreditation." And the selection of educational content, and the analysis of the characteristics of the students, and the analysis of the classroom environment, and then the researchers formulated the behavioral goals and systems of the educational content, and determined the used teaching methods, as well as the necessary educational activities, and they conducted the necessary evaluation for the proposed curriculum, so the researchers followed three types of preliminary, formative and final evaluation, and after the completion of the two researchers To build the curriculum and its requirements, they presented it in its initial form to a group of experts and arbitrators in the field of Arabic language, teaching methods, psychology, measurement and evaluation to ensure its validity. Based on the proposed approach, the current research came out with a number of conclusions, including that the use of The proposed curriculum may contribute to increasing the students' activity, effectiveness, and inclination towards General Arabic. The researchers also recommended a number of recommendations, including the adoption of the proposed curriculum in teaching General Arabic for non-specialist sections in the College of Education for Girls. The researchers suggested a number of proposals, including conducting a study similar to the current study on variables. last .